The Problem of the Applicability of Work on Fishing Convention, 2007 (C 188) in Human Trafficking in Thailand’s Fishing Industry - Jankomol, Phenpiccha (Mahachula Academic Journal, 2021)
This thesis aspires (1) to study and analyze the principles of law regarding the protection of labour in fishing work in accordance with human trafficking and forced labor under Thai law, international law, and human rights law. (2) to examine principles and problems as to the application of the Thai Law, in accordance with obligations arising from Work in Fishing Convention, 2007 (No.188). This thesis employs various legal literature including Thai legal documents concerning Human Trafficking Law and Labour Protection in Fishing Work, International Law, thesis and academic journals. The study demonstrates that Thai law has already comprised a number of Labour Protection in Fishing Work Law. Despite the current Maritime Labour Protection Act (B.E.2562) developed on Work in Fishing Convention, 2017 (No.188). It is a special law concerning Labour Protection in the fishing industry. However, in practice, there are still gaps in the law especially working conditions such as the condition in fishing, medical treatment, social security, and safety at work, etc. One main concern is that Thailand fails to comply with Work in Fishing Convention, 2017 (No.188) C188, for example, on setting the measures to prevent the fishers from Human Trafficking and on applying the law that concerns the ongoing Human Trafficking in Thailand’s fishing industry. To reduce the risk factors of forced labour and human trafficking, it includes the adoption of mechanisms and knowledge of law enforcement which the facts may lead to indications of forced labor or human trafficking of labour in fishing work. Therefore, Thailand should amend laws and regulations in accordance with C 188 to raise the standards of Thai fisheries to be equal to international standards. Moreover, the government should reduce the risk of fishers entering the cycle of human trafficking and forced labour.